Fenomena Bullying dan Dampaknya Terhadap Psikologis Remaja Pada SMP Negeri 14 Banjarbaru - Marhaeni Fajar Kurniawati; Mariana Mariana; Elis Pebtianti; Ahmad Riduan; M. Rizhan Ridha (Institut Nalanda, 2024)
Bullying is a form of intimidation by individuals or groups. This has become an issue that is attracting people’s attention nowadays because this behavior causes uncomfortable and even hurts both physically and psychologically. Many cases of bullying often happened to teenage children. And it is not uncommon for several cases to occur within the school environment. Bullying cases are widespread due to a lack of ability to control behavior and an inability to manage emotions and adapt to the environment. Some people may lack understanding of the emotional and psychological impact of bullying behavior on victims. Lack of empathy and knowledge about how their actions affect others can trigger bullying behavior. Early intervention in the form of counseling and better communication from parents and teachers to children in conditions of bullying is he best way to reduce the possibility long-term consequences.